E-SPORTS AND STUDENT ENGAGEMENT: UNDERSTANDING DIGITAL ARENA MOTIVATIONS - Dr. Mehwish Manzoor (Corresponding Author); Muhammad Ismail Wasan; Alaiqa Khadim (Journal of Religion and Society, 2025)
The rapid evolution of e-sports revolutionized the landscape of competitive gaming, attracting a vast audience and participants worldwide. This study explores the motivations behind students' engagement in e-sports, focusing on the social, entertainment, technological, financial, cognitive, and psychological factors. The research aimed to assess the perceptions of students regarding various motivational factors driving their participation in e-sports, along with examining gender-based differences in their motivations. Utilizing a quantitative approach, the study analyzed data from 515 students, with results indicating that students perceived that entertainment and fun, social interaction significantly contribute to students' involvement in e-sports. According to the findings, these elements not only operate as important engagement boosters but also show that e-sports is becoming more and more popular as a potential profession and a venue for personal growth. With implications for educational institutions, e-sports organizations, and legislators seeking to create a more welcoming and encouraging atmosphere for players, this study adds significant knowledge on the motives of students in the digital gaming space. In order to fully utilize e-sports' potential as an instrument for improving abilities and professional growth, the research also emphasizes how crucial it is to include them within educational and developmental frameworks. Keywords; E-Sports, Students, Motivation, Online Gaming, Digital Arena